ANALISIS PENGENDALIAN INTERNAL DALAM MENUNJANG EFEKTIVITAS PEMBERIAN KREDIT PADA KOPERASI KREDIT SWASTI SARI KOTA KUPANG - Tirsa Marsiana Tapatab; Wilsna Rupilu; Eugenia Hendrini P Tanan; Christian Timotius Peilouw (P3M- Politeknik Negeri Kupang, 2021)
The purpose of this researchis to find out how internal control is in supporting the effectiveness of credit distribution and to find out the effectiveness of giving credit at Koperasi Kredit Swasti Sari Kota Kupang. The research method used in this study was qualitative descriptive meanwhile the data collection techniques using interviews, observation and documentation. Researchers interviewed six (6) informants, namely the head of the internal control division, credit division, HRM division, finance division, IT and development division, and HRM staff. The results showed that the internal control of credit provision at the Koperasi Kredit Swasti Sari Kota Kupang has been implemented in accordance with the COSO internal control. The provision of credit to the Koperasi Kredit Swasti Sari Kota Kupang from 2016-2019 was in the criteria of being quite effective. The number of targets for providing credit each year increased due to the increasing number of members needs did not apply for a credit loan and also because prospective borrower members did not pass the credit application selection.